2014
DOI: 10.1248/bpb.b13-00771
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside F2 Reduces Hair Loss by Controlling Apoptosis through the Sterol Regulatory Element-Binding Protein Cleavage Activating Protein and Transforming Growth Factor-β Pathways in a Dihydrotestosterone-Induced Mouse Model

Abstract: This study was conducted to test whether ginsenoside F2 can reduce hair loss by influencing sterol regulatory element-binding protein (SREBP) cleavage-activating protein (SCAP) and the transforming growth factor beta (TGF-β) pathway of apoptosis in dihydrotestosterone (DHT)-treated hair cells and in a DHT-induced hair loss model in mice. Results for ginsenoside F2 were compared with finasteride. DHT inhibits proliferation of hair cells and induces androgenetic alopecia and was shown to activate an apoptosis si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
(24 reference statements)
3
18
0
Order By: Relevance
“…Multiple abnormalities are shown during hair loss in the hair growth cycle, including curtailed anagen and premature catagen phases, and vellus hair follicles show conversion into terminal hair follicles [17]. Couchman et al reported that fibronectin was present in the DP matrix in anagen stage hair follicles and decreased in the resting stage [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple abnormalities are shown during hair loss in the hair growth cycle, including curtailed anagen and premature catagen phases, and vellus hair follicles show conversion into terminal hair follicles [17]. Couchman et al reported that fibronectin was present in the DP matrix in anagen stage hair follicles and decreased in the resting stage [18].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that TGF-β2 inhibits hair growth not only by reducing the anagen stage but also by promoting early entry into the catagen stage [17]. Shin et al showed that ginsenoside F2 increased the proliferation of HHDPCs and reduced expression of TGF-β2 related factors and sterol regulatory element binding protein (SREBP) cleavage-activating proteins (SCAPs) involved in dihydrotestosterone-induced hair loss in vitro [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, TGF-β is the most important regulator in hair growth and the hair cycle. 33) Several studies reported that TGF-β could induce the transition of the catagen (regression) phase in the hair cycle, 34,35) indicating that the inhibition of the TGF-β pathway is associated with the promotion of hair growth.…”
mentioning
confidence: 99%
“…All 16 photographs were taken with subjects looking straight ahead under constant lighting 17 conditions with the same camera, camera settings, and camera placement. Thus, a Nikon 18 D200 camera was positioned on an SVK 35D tripod to the right of the subject's face and 19 perpendicular to the area to be photographed, while an Olympus twin T28 Macroflash unit 20 was positioned with one flash head directly above the lens pointed at the subject and the other 21 directed away. Exposure was controlled by adjusting the lens aperture with the flash set on 22 manual at full output.…”
mentioning
confidence: 99%